TEACHERS’ PERCEPTION TOWARDS THE USE OF QUIZIZZ IN ENGLISH EDUCATION DEPARTMENT AT UIN ALAUDDIN MAKASSAR - Serliah Nur; Multazam Abubakar (Universitas Islam Negeri Alauddin Makassar, 2022)
The aim of this study is to examine the teachers’ perception of using Quizizz in English Education Department at UIN Alauddin Makassar. This research was carried out by using descriptive qualitative method. The data were collected by using interview, especially semi-structured interview. The subjects of this research were two teachers of English Education Department. They were selected purposively in order to take a valid data and information. The results of this study indicate a positive perception based on the three indicators adopted, such as teachers’ knowledge, teachers’ emotion and teachers’ motivation. Overall, the researcher found that the respondents have a positive perception about Quizizz. They stated Quizizz as interactive and interesting application, they feel satisfied while using Quizizz to give students assignment and they have a desire to increase their knowledge about Quizizz. Quizizz can be used as a learning media as well as assessment media. Therefore, the respondents of this research mainly apply Quizizz to give quiz to students. Thus, the implication of this research is Quizizz can be used both as learning and assessment media in order to support learning and teaching process. However, teachers should consider the stability of internet connection before applying Quizizz in their class.